Problems of monetary policy in underdeveloped countries, with special reference to India - Hajela, P. D. (Bombay : Lalvani Pub. House, 1969)
The book examines the problems of monetary policy in underdeveloped countries especially as regards maintaining price stability. It also highlights some of the theories of monetary policy, the concepts of money supply liquidity, interest rate policy, credit control, etc.
includes index
Bibliographical footnotes.
usc 10/07/2017
Loans
Keywords: Monetary policy; Monetary policy; India